Thermodynamics of a Tetra-Stranded Genome: Stability, Thresholds, and Entropic Constraints - Barack Ndenga (Publisher, 2025)
The existence of a canonical tetra-stranded hereditary polymer requires more than structural plausibility: it must satisfy thermodynamic conditions that favor a genome-scale four-strand state over duplex or partially folded alternatives. In this work, I develop a minimal thermodynamic framework for Q-DNA, decomposing the free energy of a tetra-stranded genome into enthalpic interactions, electrostatic contributions, and entropic penalties associated with strand confinement and ordering. I derive stability thresholds as functions of temperature, ionic composition, and molecular crowding, and I predict the existence of environmental stability windows in which Q-DNA dominates the free-energy landscape. This framework provides quantitative criteria for canonicality and establishes testable predictions for experimental and synthetic realizations of tetra-stranded genomes. Keywords: Q-DNA, tetra-stranded genome, thermodynamics, free energy, entropy, electrostatics, molecular crowding
This work introduces a minimal thermodynamic framework for evaluating the feasibility of a canonical tetra-stranded hereditary genome (Q-DNA). Rather than focusing on local multistranded motifs, the manuscript analyzes genome-scale tetra-stranded architectures through a decomposition of free energy into enthalpic interactions, electrostatic contributions, and entropic penalties arising from strand confinement and ordering. The study derives thermodynamic stability thresholds relative to duplex-dominant DNA states and predicts the existence of environmental stability windows in which tetra-stranded genomes are energetically favored. These windows are defined as functions of temperature, ionic composition (notably Mg²⁺ and K⁺), and molecular crowding, highlighting regimes where electrostatic screening and confinement effects compensate for the intrinsic entropic cost of multistranded organization. By formalizing canonicality in energetic terms, this contribution provides quantitative criteria for distinguishing stable tetra-stranded genetic systems from marginal or metastable conformations. The framework establishes falsifiable predictions for synthetic genetics and biophysical experiments and informs broader discussions on alternative genetic architectures in origins-of-life research and astrobiology. Resource type: theoretical manuscript / thermodynamic model Intended audience: molecular biophysics, theoretical biology, synthetic genetics, and genome architecture communities